Republics, Revolutions and Racialisation: The South African Republic at the 1889 Paris Exposition Universelle (Historia, 2024)
This article documents and analyses the South African Republic (ZAR)’s participation in the 1889 Paris Exposition Universelle. Celebrating a century of the French Revolution and industrial development, the ZAR’s presence as an official exhibitor served as an information hub for furthering commercial and diplomatic interests in South Africa in an increasingly Anglo-German-Portuguese dominated imperial sphere. Initiated and coordinated by the French Consulate in Pretoria as a timely opportunity to alleviate the industrial uncertainties faced by Johannesburg’s mining complex, the ZAR’s participation as part of the Colonial Exhibition served as a propaganda tool for settler colonialism and the subjugation of non-Western societies. Situated among dehumanising ‘ethnographic villages’, the ZAR’s pavilion supported France’s vision of republicanism, industrialisation and racialisation at the height of the Scramble for Africa. Viewing the 1889 Paris Exposition Universelle as a major trade and information hub for industry, ethnography and imperial politics, this article analyses the ZAR’s diplomatic attempt to portray itself as a prosperous settler republic aspiring to become the world leader in the goldmining industry. As an important feature of the exhibition, the ZAR was presented as a French republican partner and symbol of colonial collaboration between a European settler society and African economies.